2012
DOI: 10.1186/1748-5908-7-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the impact of quality improvement collaboratives in mental healthcare: An exploratory study

Abstract: BackgroundQuality improvement collaboratives (QICs) bring together groups of healthcare professionals to work in a structured manner to improve the quality of healthcare delivery within particular domains. We explored which characteristics of the composition, participation, functioning, and organization of these collaboratives related to changes in the healthcare for patients with anxiety disorders, dual diagnosis, or schizophrenia.MethodsWe studied three QICs involving 29 quality improvement (QI) teams repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(71 citation statements)
references
References 22 publications
6
65
0
Order By: Relevance
“…Very few details were provided on the techniques that were taught. In some studies, the LC purveyors had already identified potential areas for improvements that sites should consider for their QI projects (e.g., domains in the chronic care model, system improvements, known implementation barriers) (7, 18, 31, 33). In addition to didactic training related to practices and QI methods, four of the studies reported that individual sites presented information to other participating QI teams during the in-person sessions (7, 15, 27, 37).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Very few details were provided on the techniques that were taught. In some studies, the LC purveyors had already identified potential areas for improvements that sites should consider for their QI projects (e.g., domains in the chronic care model, system improvements, known implementation barriers) (7, 18, 31, 33). In addition to didactic training related to practices and QI methods, four of the studies reported that individual sites presented information to other participating QI teams during the in-person sessions (7, 15, 27, 37).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies reported external support with data collection and feedback. With a few exceptions (7, 30, 33, 34, 38), most articles provided very little information about the data collected, how it was used, or how it informed quality improvement activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiences, knowledge, attitude and skills of healthcare professionals have been shown (7)(8)(9) to have an impact on the quality of wound care that they deliver to patients. Efforts to improve the quality of care have been shown to have a greater impact when healthcare professionals are provided with inspirational leadership (10). Therefore, it is important to consider how inspirational leadership can be utilised in to best effect with regards to ensure that high quality wound care is consistently delivered.…”
Section: Conflict Of Interest Nonementioning
confidence: 99%
“…Successful strategies included support from organizational management, active QI leaders, and QI team diversity (education levels, years of employment). In QI for schizophrenia, greater outcome monitoring was associated with improved patient outcomes (Versteeg et al, 2012 ).…”
Section: Quality Improvement Teamsmentioning
confidence: 99%